2012
DOI: 10.1029/2011wr011006
|View full text |Cite
|
Sign up to set email alerts
|

Interannual variability of snowmelt in the Sierra Nevada and Rocky Mountains, United States: Examples from two alpine watersheds

Abstract: [1] The distribution of snow and the energy flux components of snowmelt are intrinsic characteristics of the alpine water cycle controlling the location of source waters and the effect of climate on streamflow. Interannual variability of these characteristics is relevant to the effect of climate change on alpine hydrology. Our objective is to characterize the interannual variability in the spatial distribution of snow and energy fluxes of snowmelt in watersheds of a maritime setting, Tokopah Basin (TOK) in Cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
151
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 77 publications
(160 citation statements)
references
References 69 publications
8
151
0
1
Order By: Relevance
“…However, a longer NF season promotes reduced vegetation productivity benefits or adverse growth conditions for 51.9% of HNL grasslands and temperate forests due to summer water supply (MSI) restrictions to plant growth. Strengthening evaporative demands and more frequent summer droughts associated with earlier snowmelt and warmer summer temperatures may lead to more severe negative impacts on vegetation growth in more moisture-constrained areas (Barnett, Adam, and Lettenmaier 2005;Jepsen et al 2012). These results are similar to previous studies indicating widespread drought-induced vegetation productivity declines in northern temperate and boreal forests Piao et al 2011;Ma et al 2012).…”
Section: Discussionsupporting
confidence: 82%
“…However, a longer NF season promotes reduced vegetation productivity benefits or adverse growth conditions for 51.9% of HNL grasslands and temperate forests due to summer water supply (MSI) restrictions to plant growth. Strengthening evaporative demands and more frequent summer droughts associated with earlier snowmelt and warmer summer temperatures may lead to more severe negative impacts on vegetation growth in more moisture-constrained areas (Barnett, Adam, and Lettenmaier 2005;Jepsen et al 2012). These results are similar to previous studies indicating widespread drought-induced vegetation productivity declines in northern temperate and boreal forests Piao et al 2011;Ma et al 2012).…”
Section: Discussionsupporting
confidence: 82%
“…Also we have shown that its effect evolved during the snow accumulation and melting periods over two years having highly contrasting climatic conditions and snow accumulation amounts Many studies have analyzed the spatial distribution of SD in mountain areas considering both, intra-and inter-annual variability of the topographic control on the snowpack distribution (Anderton et al, 2004;Erickson et al, 2005;López-Moreno et al, 2010;McCreight et al, 2014). Other researches have also focused their attention in long-term interannual snow distribution analyses (Jepsen et al, 2012;Sturm and Wagner, 2010;Winstral and Marks, 2014). The results of these previous works have highlighted the difficulties in fully explaining the distribution of snow in complex mountainous terrain.…”
Section: Discussionmentioning
confidence: 99%
“…At operational sites, the seasonal variability of snow density is largely dictated by time of year, and interannual variability is typically low (Mizukami and Perica, 2008). However, previous spatial snow surveys have shown that snow density can exhibit inter-annual variability, particularly in continental regions (e.g., Balk and Elder, 2000;Jepsen et al, 2012). Snow density tends to increase gradually throughout the snow season due to crystal metamorphism, settling, and compaction.…”
Section: Snow Density Modelmentioning
confidence: 97%